Pengembangan Learning Platform Digital Kolaboratif untuk Guru Matematika SMP - Rindri, Yang Agita; Silalahi, Parulian; Fadhlilah, Husnul (Manutech : Jurnal Teknologi Manufaktur, 2025)
This study was conducted to gain deeper insight into the potential of using a digital learning platform to improve collaboration between junior high school mathematics teachers, professional development, and student learning outcomes in the context of mathematics education in junior high schools. The method used in this study was through the development and implementation of a digital learning platform that can be used collaboratively or jointly between mathematics teachers and junior high school students in Sungailiat. On the digital learning platform, teachers exchange resources and teaching activities, while students can access these resources and teaching activities. At the end of the implementation, researchers collected questionnaires to obtain information regarding the effectiveness and usefulness of the developed platform for mathematics learning in junior high schools. The measurement results on the questionnaire instrument based on the Likert scale distributed to students obtained a score of 79.37%. Meanwhile, the measurement on the teacher questionnaire obtained a score of 87.75%. Based on Sugiyono and Riduwan's interpretation categories, the range of 81% - 100% is included in the very high category and the range of 61% - 80% is included in the high category. This value shows that students and mathematics teachers have a positive view of the use of collaborative digital learning platforms in mathematics subjects for grade 7 junior high school.